# Find h'(0) if where g(0) = 3 and g'(0) = 2. h(x) = g(x) - x 3 + g(x). 12

Find h'(0) if

where g(0) = 3 and g'(0) = −2.

**Transcribed Image Text:**

## h(x) = g(x) - x 3 + g(x). 12

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

**Related Book For**

## Calculus For Business, Economics And The Social And Life Sciences

**ISBN:** 9780073532387

11th Brief Edition

**Authors:** Laurence Hoffmann, Gerald Bradley, David Sobecki, Michael Price

**Question Details**

Chapter #

**2**Section: EXERCISES 2.4

Problem: 64

## Students also viewed these Mathematics questions